2013
DOI: 10.3390/ijerph10115257
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Exposure during Childhood: Effect on Cochlear Physiology

Abstract: The rate of smoking in Brazil is about 18.8%. Exposure to environmental tobacco smoke is one of the major factors predisposing children to several hazardous health problems. The objective of the present research was to analyze the effect of tobacco smoke exposure during childhood on cochlear physiology by measuring the transient evoked otoacoustic emissions (TEOAE) response levels. Cotinine, the main metabolite of nicotine, was measured in 145 students’ (8–10 years old) urine. Sixty students indicated tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
17
1
1
Order By: Relevance
“…Moreover, TEOAEs showed lower signal to noise ratios (SNRs) at all frequency bands when the SHS group was compared to the control group (Table 6). This agreed with Durante et al, 25 that found a lower response level of TEOAEs, mainly at frequencies of 2-2.8 kHz, and also lower signal to noise ratios (SNRs), mainly at 1-1.4 kHz, in the children with SHS when compared to the non-exposed one. Also, Paschoal & Azevedo 27 stated that the reduction in TEOAEs was found at 1 kHz, similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, TEOAEs showed lower signal to noise ratios (SNRs) at all frequency bands when the SHS group was compared to the control group (Table 6). This agreed with Durante et al, 25 that found a lower response level of TEOAEs, mainly at frequencies of 2-2.8 kHz, and also lower signal to noise ratios (SNRs), mainly at 1-1.4 kHz, in the children with SHS when compared to the non-exposed one. Also, Paschoal & Azevedo 27 stated that the reduction in TEOAEs was found at 1 kHz, similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
“…SHS exposure in childhood is proposed to affect the physiology of the cochlea by distressing the outer hair cells which can be accessed through a decreased in (TEOAE) response. 25 In the current study, 64 ears of the study group had a total pass; on the other hand, there were 30%with a partial pass and 6% with failed TEOAE (Table 5). Moreover, TEOAEs showed lower signal to noise ratios (SNRs) at all frequency bands when the SHS group was compared to the control group (Table 6).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It was previously reported that smokers were more likely to have prevalent HI (odds ratio = 1.69, 95% confidence interval (CI) = 1.31–2.17) in the population‐based Epidemiology of Hearing Loss Study (EHLS) . Higher circulating levels of reactive oxygen species or inflammatory markers and atherosclerotic changes associated with smoking may damage the cochlea or result in neurodegeneration . Other cross‐sectional population‐based studies also have reported associations between smoking and prevalent HI .…”
mentioning
confidence: 99%
“…A PTA é um risco para a saúde não apenas para os fumantes, mas também para os fumantes passivos, principalmente para as crianças (DURANTE et al, 2013;JOYA et al, 2014). Trabalhos anteriores de nosso grupo mostram que a exposição de camundongos à PTA no início do período pós-natal induz estresse oxidativo em diferentes regiões encefálicas (TORRES et al, 2012), além de danos ao processo de mielinização no nervo óptico e diminuição das proteínas Olig-1 e proteína básica de mielina (TORRES et al, 2014).…”
Section: Poluição Tabagística Ambientalunclassified